MODELING AND GEOTECHNICAL ZONING OF GEOTECHNICAL PROPERTIES OF SOILS IN FERGANA REGION - Khakimova Kamola Rakhimjonovna; Imomaliyeva Zarnigor Oybek kizi (European Science Publishing, 2025)
This in the article Soils of the Fergana region modeling geotechnical properties and the area geotechnical risk to the level see zoning according to scientific and methodological approach has been developed. First of all, the field and laboratory tests results ( φ , c, E, g , Cc, cv and others) based on geotechnical information base formed, each X, Y, Z coordinates for a point, soil type, layer code, experiment ( X_test ), characteristic ( X_k ) and computational ( X_d ) parameters one to the system was brought. Then geostatistician methods – variogram analysis and kriging interpolation – using of parameters spatial distribution modeled by , φ , c, E, Cc, cv isoline and superficial maps created. Geotechnical parameters layers in a GIS environment land under water level, salinity, relief slope, seismic zoning such as thematic layers with integration geotechnical and seismogeotechnics risk level complex was evaluated. As a result, By Fergana region relatively comfortable, careful approach required and geotechnical in terms of complicated zones separated and every for one zone research size, foundation types choice and additional constructive measures according to recommendations have been developed. Proposal done approach province on a scale territorial planning, new construction and infrastructure projects geotechnical in terms of in justification application possible was effective scientific and practical the platform shapes.
Keywords: Fergana region, soil geotechnical properties , geotechnical modeling , geotechnical zoning , geostatistics , variogram , kriging, GIS technologies , geotechnical information base , geotechnical risk , seismogeotechnical assessment.